Effect of service quality and student satisfaction on academic information system usage effectiveness - Aulia Oktariani; Nellitawati Nellitawati; Ahmad sabandi; Rusdinal Rusdinal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study analyzes the influence of academic administrative service quality and user satisfaction on the effectiveness of Academic Management Information System (SIMA) usage in higher education. Service quality was evaluated using the SERVQUAL dimensions, while user satisfaction was assessed through four key indicators. A quantitative survey of 333 students, supported by qualitative interviews, was employed. Multiple regression analysis shows that service quality significantly affects SIMA usage (β = 0.379; p = 0.000), and user satisfaction also has a strong positive effect (β = 1.053; p = 0.000). Together, both variables explain 47% of the variance in SIMA usage (R² = 0.470). Descriptive findings indicate that assurance and responsiveness are the weakest aspects of service quality, while the confirmation dimension requires attention within user satisfaction. Although system and information quality are generally rated well, issues remain regarding information relevance and system assurance. Overall, the study highlights the need for a holistic strategy that simultaneously enhances service quality and user satisfaction to improve SIMA effectiveness in supporting academic processes